Factors of Psychological Well – being and Models of ideal and real Psychological Well - being - Kalvāns, Ēriks (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article deals with the phenomenon of psychological wellbeing and factors influencing it. There are described contemporary approaches of social pedagogy to the interpretation of the phenomenon of social wellbeing and there are analyzed factors influencing it in the paradigm of positive psychology. The publication also reflects the results of the research aimed at exploration of factors influencing ideal and real psychological wellbeing according to which there are created models of ideal and real psychological wellbeing.